The Russian-Ukrainian War (2022): A Reading of the Causes and Possible Future Scenarios - Shnikat, Khaled H.; Al khraisha, Khaled R. (Dirasat: Human and Social Sciences, 2024)
Objectives: This study examines the causes and motives of the Russian-Ukrainian War through focusing on the historical dimension of the crisis, the parties involved in the war, their relevant interests, and strategic visions. The study also touches on the possible scenarios of the war. Methods: The study attempts to answer two questions: First, what are the respective Russian and Ukrainian interests? Second, how can we account for the current war in accordance with those interests? To answer these two questions, the study utilized the hypotheses of the realistic school to provide an understanding of the topic in question, as it is the best suited method for analyzing the dynamics of power and national interests as well as the conflicts that result from such dynamics. Results: The study shows that the outbreak of the war was due to Russia’s fears of Ukraine’s accession to NATO and the European Union. Such accession places NATO on Russia’s borders, a situation that threatens the security of Russia (as perceived by its leaders), especially given the potential deployment of NATO missiles in the region. The study also points to the potential negative impact of the war on the parties involved. Conclusions: The study concludes that this conflict may turn into a war of attrition for Russia, as it will accrue devastating costs to both Russia and Ukraine, and even NATO countries.